GAMBARAN KEJADIAN MOLA HIDATIDOSA PADA KEHAMILAN DI INDONESIA - Saida Saida (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
The maternal mortality rate in Indonesia is still relatively high, with the highest cause being bleeding. Hydatidiform mole can be one of the causes because the main complaint of hydatidiform mole is vaginal bleeding. Purpose To find the incidence and characteristics of patients with hydatidiform mole. There were 6 articles that were considered eligible which were filtered out of 1580 using the keywords “Hydatidiform mole”, “Pregnancy”. Characteristics of hydatidiform mole sufferers such as hypertension during pregnancy, malnutrition during pregnancy, bleeding during pregnancy, pregnant women <20 years and above 35 years, high parity.